Lipid Quality of Amazonian’s Native Fish, Overview and Market Outlook of Brazilian Fish Farming (Revista Brasileira Multidisciplinar, 2024)
The aimed of this study was to carry out a bibliometric survey on the lipid composition Amazonian’s native fish and the international aquaculture overview, Brazilian aquaculture overview, native farmed fish production, characteristics of Brazilian fish meat, nutritional aspects and benefits of native fish consumption and market outlook of Brazilian fish farming. This is a data collection study that is characterized as being of an exploratory descriptive, with a qualitative character, aiming to analyze, systematize, compare and cross data between different scientific literatures related to the theme. The searches in Web, storage and data analysis were carried out from March to August 2021. The bibliographic bases for carrying out the searches were Scopus, Web Science, Elsevier, Hindawi, Scielo, Wiley, CAPES/Brasil Journals and institutional repositories. Searched for descriptors in Portuguese and English language, with words and terms separated by the Boolean operators 'AND' and 'OR'. In addition to being sustainable, consuming native farmed fish is a healthy choice from a nutritional point of view, because they contain monounsaturated and polyunsaturated fatty acids that are related to an anti-inflammatory effect and a lower propensity for cardiovascular diseases in consumers. Regarding the production chain problems, market studies must be carried out for each region of Brazil. In addition, more investment in integrated crop systems is needed. In other words, quality certification is needed to universalize native Brazilian fish. Therefore, the future of Brazilian fish will depend on better dissemination to attract different market niches
Keywords: Brazilian native farmed fish; food safety; healthy food